Development of the Synarcual in the Elephant Sharks (Holocephali; Chondrichthyes): Implications for Vertebral Formation and Fusion - Johanson, Z.; Boisvert, C.; Maksimenko, A.; Currie, P.; Trinajstic, Katherine (PUBLIC LIBRARY SCIENCE, 2015)
The synarcual is a structure incorporating multiple elements of two or more anterior vertebrae of the axial skeleton, forming immediately posterior to the cranium. It has been convergently acquired in the fossil group ‘Placodermi’, in Chondrichthyes (Holocephali, Batoidea), within the teleost group Syngnathiformes, and to varying degrees in a range of mammalian taxa. In addition, cervical vertebral fusion presents as an abnormal pathology in a variety of human disorders. Vertebrae develop from axially arranged somites, so that fusion could result from a failure of somite segmentation early in development, or from later heterotopic development of intervertebral bone or cartilage. Examination of early developmental stages indicates that in the Batoidea and the ‘Placodermi’, individual vertebrae developed normally and only later become incorporated into the synarcual, implying regular somite segmenta- tion and vertebral development. Here we show that in the holocephalan Callorhinchus milii, uniform and regular vertebral segmentation also occurs, with anterior individual vertebra developing separately with subsequent fusion into a synarcual. Vertebral elements forming directly behind the synarcual continue to be incorporated into the synarcual through growth. This appears to be a common pattern through the Vertebrata. Research into human disor- ders, presenting as cervical fusion at birth, focuses on gene misexpression studies in humans and other mammals such as the mouse. However, in chondrichthyans, vertebral fusion represents the normal morphology, moreover, taxa such Leucoraja (Batoidea) and Callorhinchus (Holocephali) are increasingly used as laboratory animals, and the Callor- hinchus genome has been sequenced and is available for study. Our observations on synarcual development in three major groups of early jawed vertebrates indicate that fusion involves heterotopic cartilage and perichondral bone/mineralised cartilage developing outside the regular skeleton. We suggest that chondrichthyans have potential as ideal extant models for identifying the genes involved in these processes, for application to human skeletal heterotopic disorders.